Lack of pathogenic mutations in SOS1 gene in phenytoin-induced gingival overgrowth patients. (August 2017) - Margiotti, Katia; Pascolini, Giulia; Consoli, Federica; Guida, Valentina; Di Bonaventura, Carlo; Giallonardo, Anna Teresa; Pizzuti, Antonio; De Luca, Alessandro
Abstract: Objective: Gingival overgrowth is a side effect associated with some distinct classes of drugs, such as anticonvulsants, immunosuppressants, and calcium channel blockers. One of the main drugs associated with gingival overgrowth is the antiepileptic phenytoin, which affects gingival tissues by altering extracellular matrix metabolism. It has been shown that mutation of human SOS1 gene is responsible for a rare hereditary gingival fibromatosis type 1, a benign gingival overgrowth. The aim of the present study is to evaluate the possible contribution of SOS1 mutation to gingival overgrowth-related phenotype. Design: We selected and screened for mutations a group of 24 epileptic patients who experienced significant gingival overgrowth following phenytoin therapy. Mutation scanning was carried out by denaturing high-performance liquid chromatography analysis of the entire coding region of the SOS1 gene. Novel identified variants were analyzed in-silico by using Alamut Visual mutation interpretation software, and comparison with normal control group was done. Results: Mutation scanning of the entire coding sequence of SOS1 gene identified seven intronic variants and one new exonic substitution (c.138G > A). The seven common intronic variants were not considered to be of pathogenic importance. The exonic substitution c.138G > A was found to be absent in 100 ethnically matched normal control chromosomes, but was not expected to have functional significance based on prediction bioinformatics tools. Conclusions: This study represents the first mutation analysis of the SOS1 gene in phenytoin-induced gingival overgrowth epileptic patients. Present results suggest that obvious pathogenic mutations in the SOS1 gene do not represent a common mechanism underlying phenytoin-induced gingival overgrowth in epileptic patients; other mechanisms are likely to be involved in the pathogenesis of this drug-induced phenotype.